Stabilization and spectral properties of acoustic flow in a cylindrical shell. Issue 1 (2nd January 2022) - Lee, Doo-Sung
ABSTRACT: In this paper, we present a fully coupled mathematical model describing the interaction between a thin cylindrical shell and an enclosed acoustic field. We prove the uniqueness of the solution which can be described by semi-group theory. We also use the perturbation theory to study the spectral properties of the three-dimensional acoustic flow. Asymptotic values, when time approaches to infinity, are given.